Ethical Questions in Medical Electronic Adherence Monitoring - Campbell, Jeffrey I.; Eyal, Nir; Musiimenta, Angella; Haberer, Jessica E. (Journal of general internal medicine, 2015)
Electronic adherence monitors (EAMs) record and report an array of health behaviors, ranging from taking daily medications to wearing medical devices. EAMs are utilized in research worldwide and are being investigated for clinical use. However, there is also growing popular concern about the extent to which electronic devices may be used to monitor individuals, including allegations in the media that EAMs represent a move towards BBig Brother^ in medicine. Here, we highlight the unique benefits as well as the potential ethical challenges that electronic adherence monitoring generates. These challenges surround autonomy, privacy and confidentiality, trust, and ancillary care obligations. We describe key questions within each of these domains that warrant further investigation, and present potential solutions to many of the concerns raised.
Keywords: Electronic adherence monitoring; Patient adherence; Privacy; Confidentiality; Personal autonomy; research ethics.